A location-price-based buyer coalition - Narabin, Santit; Boonjing, Veera (My University, 2012)
A buyer coalition is a group of buyers who join together to negotiate with sellers to purchase items for a larger discount. In this article, a novel buyer coalition scheme, called the "GroupSimilarBuyer Scheme, " is introduced. The new idea focuses on buyer coalition formation based on similarity of buyers. The mechanism of approach begins to prepare data for driving the next step. Then, a k-mean clustering algorithm is used to form the coalition of buyers which are very similar in both reservation price and location of buyer. In addition, the utility of each buyer coalition is calculated. Based on the simulation result, the GroupSimilarBuyer showed that the average standard deviation of the coalition was nearly the optimum result. © 2012 IEEE.
Keywords: buyer coalition; coalition formation; electronic commerce; group-buying; GroupSimilarBuyer